The accentedness, comprehensibility, and intelligibility of Asian Englishes. Issue 4 (11th September 2018) - Hansen Edwards, Jette G.; Zampini, Mary L.; Cunningham, Caitlin
Abstract: This study examines the accentedness, comprehensibility, and intelligibility of speakers of English from China, Hong Kong, Singapore, and the United States (US) by listeners from Hong Kong, Singapore, China, and the US on two speech tasks (read vs. conversation). It also examines the effect of shared background on scores for all listeners as well as the effect of international experience for the Hong Kong and the US listeners. The study found that although accentedness and comprehensibility were positively correlated, neither variable was significantly correlated with intelligibility. The study found that shared background increased ratings of accentedness and comprehensibility but not intelligibility scores, and that international experience also had an effect during the conversational task, in that listeners with international experience received significantly higher intelligibility scores than those without any such international experience.